UPAYA LPMD DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DI DESA PUSAT DAMAI KABUPATEN SANGGAU - Januardi Pabayo, Roymundus; Okianna, Okianna; Kuswanti, Heni (Universitas Tanjungpura, 2025)
This research aims to find out and explore what efforts have been and will be made by the Village Community Empowerment Institution (LPMD) in collaboration with the Village Government to improve the economic welfare of the community in the Peace Center Village. This research uses a qualitative approach with a case study method. The resource persons in this research were LPMD administrators, village government and the community. The data collection techniques used in this research are interviews, observation and documentation. The research results show that the development and empowerment efforts carried out have been ongoing and have had a good impact in improving the economic welfare of the community. Efforts are made in the form of community empowerment in the form of agricultural groups, fisheries groups and community market provision. However, there are shortcomings in LPMD members who do not understand their duties and responsibilities as an institution in society. This is also caused by a lack of training and understanding of LPMD members regarding their duties and functions. This has an impact on the slowness of the empowerment process.